A triangulated approach for understanding scientists' perceptions of public engagement with science. (April 2023) - Calice, Mikhaila N.; Bao, Luye; Beets, Becca; Brossard, Dominique; Scheufele, Dietram A.; Feinstein, Noah Weeth; Heisler, Laura; Tangen, Travis; Handelsman, Jo
Scientists are expected to engage with the public, especially when society faces challenges like the COVID-19 pandemic or climate change, but what public engagement means to scientists is not clear. We use a triangulated, mixed-methods approach combining survey and focus group data to gain insight into how pre-tenure and tenured scientists personally conceptualize public engagement. Our findings indicate that scientists' understanding of public engagement is similarly complex and diverse as the scholarly literature. While definitions and examples of one-way forms of engagement are the most salient for scientists, regardless of tenure status, scientists also believe public engagement with science includes two-way forms of engagement, such as citizen and community involvement in research. These findings suggest that clear definitions of public engagement are not necessarily required for its application but may be useful to guide scientists in their engagement efforts, so they align with what is expected of them.